Rom 15,7-13 Revisited: Purposes and Proofs - Granados Rojas, Juan Manuel (Biblica, 2021)
Casson’s recent monograph has brought to attention the importance of the interpretation of γάρ in Rom 15,8. This paper delves into the correlated subjects: the γάρ-δέ construction in vv. 8a-9a, the anti-imperial reading, and the inner coherence of the scriptural catena within vv. 7b-12. The syntax of the prepositional construction (εἰς τό + infinitive) in v. 8b and the infinitive verbs (βεβαιῶσαι and δοξάσαι) in vv. 8b-9a do not indicate an interruption in the flow of thought between the subjects 'Christ' and 'the Gentiles', but an argumentative incrementum that articulates proofs and purposes.